Three component terpolymer and IPN hydrogels with response to stimuli - Alzari, Valeria; Ruiu, Andrea; Nuvoli, Daniele; Sanna, Roberta; Martinez, Javier Illescas; Appelhans, Dietmar; Voit, Brigitte; Zschoche, Stefan; Mariani, Alberto (Polymer, 2014)
Two different types of multi-stimuli-shrinking hydrogels were synthesized (IPNs and terpolymeric hydrogels) by properly polymerizing N-isopropylacrylamide, 2-hydroxyethyl methacrylate and 2-acrylamido-2-methylpropanesulfonic acid in various mutual ratios and different synthetic orders. Both classical (CP) and frontal (FP) polymerizations were used and the resulting material properties compared. The best compositions and synthetic routes were found and the swelling, morphological and thermal material properties were studied. The results show that some IPNs exhibit marked stimuli-shrinking properties while some terpolymers present an opposite behavior. IPNs swell more than terpolymers and show a sharper stimuli-response, with a larger swelling ratio variation. In addition, FP allowed obtaining samples with the same characteristic of CP materials, but with significant preparation advantages. It has been demonstrated that by varying monomer mutual ratio, synthetic technique (FP or CP) and structural architecture (terpolymers or IPNs), different materials having peculiar properties and characteristics can be obtained.
CRIS-Team Scopus Importer:2023-03-20
Keywords: Frontal polymerization; IPNs; Stimuli-responsive hydrogels